Application of tagging for the investigation of salmon smolts after their descent into the Gulf of Riga - Mitans, A.R. (Baltijskij Nauchno-issledovatelskij Institut Rybnogo Khozyajstva; "Zvaigzne", 1970)
From 1964 to 1966 the descent of salmon (Salmo salar) smolts was traced and their abundance estimated in the Salaca River (Latvia) discharging into the eastern part of the Gulf of Riga (Baltic Sea). The tagging allowed to follow migrations of the smolts, their mortality caused by fishing gears and the growth rate at the early period of life in the Gulf of Riga. Owing to the loss of tags the method was not suitable for calculations of the return rate. It was suggested to use the Swedish method of fastening of the tags in future. Published Not Known